Isolation and characterisation of lytic bacteriophages for biological control of Salmonella spp. (Enterobacteriaceae) in raw vegetables (lalapan) - Affan Gaffar; Ziana Warsani (Bioma, 2026)
Salmonella spp. contamination in fresh vegetables, particularly those consumed raw without heat treatment, poses a significant food safety risk. Lytic bacteriophages offer promise as biological control agents due to their ability to specifically lyse target bacteria. This study aimed to isolate and characterise lytic bacteriophages active against Salmonella spp. from raw vegetables. Samples of lettuce (Lactuca sativa), eggplant (Solanum melongena), cabbage (Brassica oleracea var. capitata), and basil (Ocimum basilicum) were collected from local markets and processed using the double-layer agar method. Two bacteriophage isolates were recovered: SLSp from lettuce and TRSp from eggplant, while no plaques were detected in cabbage or basil. Host range analysis revealed that both isolates lysed only Salmonella spp., with no activity against Bacillus cereus, Escherichia coli, or Staphylococcus aureus. SLSp exhibited a higher titer (2.2 × 10⁵ PFU/mL) than TRSp (8.9 × 10⁴ PFU/mL). Both isolates remained active at 30°C and neutral pH but showed reduced lytic activity at 60–80°C and under extreme pH conditions (2 and 12). These findings indicate that SLSp and TRSp are promising candidates for development as biocontrol agents against Salmonella in fresh foods.